Silver paste for ultrasonic fingerprint module and preparation method thereof

By using a specific ratio of silver paste in the ultrasonic fingerprint module, the problems of insufficient conductivity, leveling and density of silver paste in the prior art are solved, and more efficient ultrasonic signal transmission and more accurate fingerprint recognition are achieved.

CN119852005AActive Publication Date: 2025-04-18NANO TOP ELECTRONICS TECH

Patent Information

Application Number
CN202510308984.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-18
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing silver paste used in ultrasonic fingerprint modules has shortcomings in electrical conductivity, leveling, low temperature curing and density, resulting in low signal transmission efficiency and recognition accuracy.

Method used

A silver paste containing epoxy resin, curing agent, curing accelerator, dispersant, organic solvent, coupling agent and spherical silver powder is used to ensure high conductivity, low surface roughness and high density of the silver paste through specific ratios and preparation methods.

Benefits of technology

The silver paste is achieved with low curing temperature, low square resistance, low surface roughness and high density, and the transmission efficiency of ultrasonic signals and the accuracy of fingerprint recognition are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses silver paste for an ultrasonic fingerprint module and a preparation method of the silver paste, and belongs to the technical field of fingerprint recognition. The conductive silver paste comprises the following raw materials: 2%-15% of epoxy resin, 0.5%-2% of a curing agent, 0.01%-0.5% of a curing accelerator, 0.5%-2% of a dispersing agent, 2%-20% of an organic solvent, 0.1%-0.3% of a coupling agent, 65%-85% of spherical silver powder and 0.03%-1.35% of a thixotropic agent. The raw materials are subjected to graded stirring, filtering and vacuum dispersion, and the silver paste for the ultrasonic fingerprint module is prepared. Through the compounding effect of the raw materials, the finally prepared silver paste has the advantages of low curing temperature, low sheet resistance, low surface roughness, high density, no layering after lamination and no large-size holes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fingerprint recognition technology, and particularly relates to a silver paste for ultrasonic fingerprint modules and its preparation method. Background Technology

[0002] Ultrasonic fingerprint modules utilize ultrasonic waves to detect the three-dimensional structure of fingerprints, providing a higher level of recognition accuracy and security. They can penetrate the epidermis to capture deeper fingerprint details, effectively distinguishing genuine fingerprints from forged ones, significantly improving system security compared to traditional fingerprint recognition technologies. Furthermore, they offer greater environmental adaptability. For example, they can accurately identify fingerprints with wet or dirty hands, unaffected by common contaminants such as water, oil, and hand cream. This allows ultrasonic fingerprint modules to maintain stable performance in various application scenarios, such as outdoor environments or industrial production. As technology continues to advance, consumers demand higher security and convenience from smart devices. Ultrasonic fingerprint modules, as an innovative biometric technology, meet the market's pursuit of higher performance and a more convenient experience. Their emergence provides a more advanced unlocking solution for products such as smartphones and smart locks, enhancing the user experience.

[0003] Silver paste plays a crucial role in ultrasonic fingerprint modules, for example:

[0004] 1. High Conductivity Requirement: The silver paste in ultrasonic fingerprint modules possesses excellent conductivity, enabling efficient transmission of ultrasonic signals. In ultrasonic fingerprint modules, an ultrasonic transducer needs to be driven by an electrical signal to receive the reflected ultrasonic signals. The high conductivity of the silver paste ensures efficient and stable signal transmission, improving the accuracy and response speed of fingerprint recognition.

[0005] 2. Excellent leveling and printability: The ultrasonic fingerprint module silver paste can be applied to specific areas of the fingerprint module through printing processes. It has excellent leveling properties, resulting in an extremely low surface roughness. This reduces noise during ultrasonic signal transmission, thereby improving the timeliness and accuracy of ultrasonic signal transmission. Furthermore, its excellent printability allows the ultrasonic fingerprint module silver paste to adapt to complex geometries, intricate circuit designs, and varying degrees of layering during the manufacturing process of the ultrasonic fingerprint module, thus achieving high integration and miniaturization.

[0006] 3. Low-temperature curing and density: The silver paste for ultrasonic fingerprint modules needs to be cured at a low temperature with high density. This is mainly due to the fact that the substrate is a non-temperature-resistant PVDF material, which determines that the curing temperature of the silver paste is below 100℃. In order to achieve fast and stable ultrasonic signal transmission, the silver paste is required to be highly dense. Otherwise, it will cause signal attenuation, which will ultimately result in poor unlocking sensitivity and accuracy.

[0007] However, existing silver pastes for ultrasonic fingerprint modules still have the following problems. For example, the materials used to make conductive electrodes are usually a mixture of large silver particles, film carriers and solvents. The mixing is insufficient, and the cured material is unevenly distributed and has low density. Or the raw material components are difficult to compound, which results in delamination and large-sized pores after lamination. Or the curing temperature of the silver paste is high, resulting in high sheet resistance, which affects its conductivity as a conductive material.

[0008] In summary, in the application of ultrasonic fingerprint modules, silver paste needs to meet characteristics such as high conductivity, high leveling, low roughness, low temperature curing, and high density. These high standards for silver paste make the development of a silver paste for ultrasonic fingerprint modules an indispensable key in ultrasonic fingerprint recognition technology. Summary of the Invention

[0009] To address the aforementioned technical problems, this invention proposes a silver paste for ultrasonic fingerprint modules and its preparation method.

[0010] To achieve the above objectives, the present invention provides the following technical solution:

[0011] One of the technical solutions of this invention:

[0012] A silver paste for ultrasonic fingerprint modules, comprising, by weight percentage:

[0013] The composition includes: epoxy resin 2%-15%, curing agent 0.5%-2%, curing accelerator 0.01%-0.5%, dispersant 0.5%-2%, organic solvent 2%-20%, coupling agent 0.1%-0.3%, spherical silver powder 65%-85%, and thixotropic agent 0.03%-1.35%.

[0014] The epoxy resin is bisphenol A epoxy resin.

[0015] Preferably, the spherical silver powder is micron-sized silver powder with a D50 of 1-2 μm and a D100 of 3-5 μm;

[0016] The mass ratio of epoxy resin to spherical silver powder is 7:74.

[0017] Preferably, the curing accelerator comprises an acetylacetone metal salt; further, the acetylacetone metal salt comprises zirconium acetylacetone, copper acetylacetone, or cobalt acetylacetone; more preferably, it is zirconium acetylacetone.

[0018] Beneficial effects: This invention limits the use of acetylacetone metal salt as a curing accelerator to react with epoxy resin. The specific reaction mechanism is as follows: the metal ions (zirconium ions) in zirconium acetylacetone have empty orbitals, which can form coordination complexes with epoxy groups in epoxy resin to catalyze polymerization. During the reaction, the metal ions not only participate in coordination catalysis, but also significantly improve the reaction rate and curing efficiency of epoxy resin through other mechanisms (such as ionic effects, electronic effects, etc.). This results in a denser cured silver paste, changes the molecular structure of epoxy resin, obtaining a more load-bearing network structure, and makes the silver powder more evenly distributed in the resin. It can also effectively improve the delamination problem during the silver paste lamination process.

[0019] Preferably, the curing agent includes one or more of dicyandiamide, blocked isocyanate, or latent imidazole modifier.

[0020] Preferably, the dispersant is one or more of polyether phosphate, oleic acid, TDO (Duomeen TDO pigment dispersant), or lauryl phosphate. More preferably, the dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1.

[0021] Beneficial effects: The addition of the above-mentioned dispersant during the silver paste preparation process in this invention gives the silver powder extremely high interfacial stability activity, enabling it to be uniformly dispersed in the resin solution and effectively solving the particle agglomeration effect (for example, the polymer segments in the TDO dispersant fully expand in the solvent, forming a protective layer covering the surface of the silver powder particles. When two silver powder particles approach each other, the polymer segments on their surfaces generate a steric hindrance effect, preventing further approach and agglomeration between the particles); and it can effectively repel moisture adsorption at the substrate interface, improve the adhesion of the coated product, reduce the interfacial energy between the substrate and the silver paste, and between silver pastes, providing a good channel for ultrasonic transmission.

[0022] Preferably, the organic solvent is one or more of DBE (divalent ester), dimethyl adipate, 3-methoxybutyl acetate, diethyl adipate, 3-methoxybutyl acetate, or propylene glycol methyl ether acetate.

[0023] Preferably, the coupling agent is one or more of the following: silane coupling agent, titanate coupling agent, aluminate coupling agent, bimetallic coupling agent, phosphate coupling agent, or borate coupling agent.

[0024] Beneficial effects: The coupling agent specified in this invention enables good contact between the slurry and the substrate, reduces the difficulty of electron transition, and increases the frequency of bridging between conductive silver powder particles, resulting in better conductivity and better transmission of ultrasonic signals. Furthermore, it works synergistically with the curing accelerator specified in this invention to improve the curing degree of the slurry, reduce the porosity of the slurry, and significantly increase the density of the silver paste, thereby greatly improving the transmission efficiency of ultrasonic signals.

[0025] Preferably, the thixotropic agent includes one or more of fumed silica, organobentonite, polyamide wax, asbestos, and kaolin.

[0026] Beneficial effects: The thixotropic agents (such as fumed silica, organobentonite, etc.) used in this invention form a three-dimensional network structure with other raw materials in the system through physical or chemical interactions. These network structures are stable through interactions such as hydrogen bonds and van der Waals forces. When the system is subjected to external forces (such as stirring, coating, etc.), the network structure is disrupted, leading to a decrease in system viscosity and an increase in fluidity. After the external force is removed, the network structure is rapidly restored, and the system viscosity increases accordingly, returning to its original state.

[0027] The second technical solution of the present invention:

[0028] The above-mentioned method for preparing silver paste includes the following steps:

[0029] The epoxy resin and organic solvent were mixed evenly according to the weight percentage to obtain the primary carrier;

[0030] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the primary carrier, stir once, and then grind with three rollers to obtain the secondary carrier;

[0031] Spherical silver powder is added to the secondary carrier, and the mixture is stirred twice, then milled in a three-roll mill, filtered in a filter press, and then vacuum dispersed to obtain the silver paste.

[0032] Preferably, the conditions for both the primary and secondary mixing processes are: placing the mixture in a double planetary mixer and mixing it at a speed of 50-100 / 1000-2000 rpm.

[0033] Preferably, the filtration is through a mesh size of 800-2000.

[0034] Beneficial effects: The preparation method of this invention limits the filtration to a high mesh size of 800-2000 mesh, which helps to obtain uniform small-sized silver paste particles, improve the fineness of the silver paste, and obtain a silver paste fineness of less than 1μm (test results using a scraper fineness meter). Under electron microscopy, the silver paste particle size after curing is less than 5μm.

[0035] Preferably, the conditions during the vacuum dispersion process are: dispersion at 200-1000 rpm for 10-30 min under 1-5 kPa conditions.

[0036] Beneficial effects: Vacuum dispersion under the conditions specified in this invention helps to eliminate air bubbles introduced during the silver paste production process, resulting in a 50-80% reduction in the porosity (>1μm) of the cured silver paste.

[0037] Compared with the prior art, the present invention has the following advantages and technical effects:

[0038] This invention adds bisphenol A epoxy resin, epoxy resin curing agent, curing accelerator, conductive silver powder with a particle size of less than 5μm, and a variety of organic solvents and additives to the conductive silver paste, so that the final silver paste has the advantages of low curing temperature, low sheet resistance, low surface roughness, high density, and no delamination or large-sized pores after lamination. Detailed Implementation

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0041] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0042] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0043] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0044] This invention discloses a low-temperature conductive silver paste for ultrasonic fingerprint modules, comprising the following components by mass percentage:

[0045] The composition includes: epoxy resin 2%-15%, curing agent 0.5%-2%, curing accelerator 0.01%-0.5%, dispersant 0.5%-2%, organic solvent 2%-20%, coupling agent 0.1%-0.3%, spherical silver powder 65%-85%, and thixotropic agent 0.03%-1.35%.

[0046] The epoxy resin is bisphenol A epoxy resin, purchased from Mitsubishi Japan, model number JER1256.

[0047] In some preferred embodiments, the curing agent includes one or more of dicyandiamide, blocked isocyanate, or latent imidazole modifier.

[0048] In some preferred embodiments, the curing accelerator includes one or more of DBU octanoate, modified imidazole, metal acetylacetone salt, or boron trifluoride complex.

[0049] In some preferred embodiments, the spherical silver powder is micron-sized silver powder with a D50 of 1-2 μm and a D100 of 3-5 μm.

[0050] In some preferred embodiments, the organic solvent is one or more of DBE, dimethyl adipate, 3-methoxybutyl acetate, diethyl adipate, 3-methoxybutyl acetate, or propylene glycol methyl ether acetate.

[0051] In some preferred embodiments, the dispersant is one or more of polyether phosphate, oleic acid, TDO, or lauryl phosphate.

[0052] In some preferred embodiments, the coupling agent is one or more of the following: silane coupling agent, titanate coupling agent, aluminate coupling agent, bimetallic coupling agent, phosphate coupling agent, or borate coupling agent.

[0053] Furthermore, this invention also provides a method for preparing the low-temperature conductive silver paste for ultrasonic fingerprint modules described above, comprising the following steps:

[0054] According to the weight percentage, the epoxy resin and organic solvent are dissolved at a temperature of 70-80℃ and mixed evenly to obtain the first mixture;

[0055] After adding curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the first mixture above, stir evenly and then perform three-roll milling to obtain the second mixture;

[0056] After adding spherical silver powder to the second mixture, stir it evenly, perform three-roll milling, filter it in a filter press at 800-2000 mesh, and then vacuum disperse the silver paste at 200-1000 rpm / 10-30 min / 1-5 kPa to finally prepare the low-temperature conductive silver paste for ultrasonic fingerprint modules.

[0057] All raw materials used in this invention were purchased from the market.

[0058] The technical solution of the present invention will be further illustrated by the following embodiments.

[0059] Example 1

[0060] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 8% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 11.6% organic solvent, 0.2% coupling agent, 78% spherical silver powder, and 0.25% thixotropic agent.

[0061] The epoxy resin is bisphenol A epoxy resin;

[0062] The curing agent is a latent imidazole modified compound, Asahi Kasei 9322;

[0063] The curing accelerator is zirconium acetylacetonate, CAS: 17501-44-9;

[0064] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0065] The coupling agent is a silane coupling agent, Dow Corning 6040;

[0066] The organic solvent is a mixture of DBE and diethyl adipate, with a mass ratio of 1:2.

[0067] Spherical silver powder has a D50 of 1-2 μm and a D90 of 3-5 μm.

[0068] The thixotropic agent is Wacker H2O.

[0069] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0070] Epoxy resin and organic solvent were mixed in a glass stirred tank for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier; the stirring speed was 350 rpm.

[0071] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, and then mix them at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the fineness of the slurry reaches below 5 μm, thus obtaining the secondary carrier;

[0072] After adding spherical silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then ground by three roller mills, filtered through a filter press at 2000 mesh, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0073] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 18mΩ / □ / mil.

[0074] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 2.7μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0075] Example 2

[0076] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 15.6% organic solvent, 0.2% coupling agent, 75% silver powder, and 0.25% thixotropic agent.

[0077] The epoxy resin is bisphenol A epoxy resin;

[0078] The curing agent is Asahi Kasei K60X;

[0079] The curing accelerator is CAS: 17501-44-9;

[0080] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0081] The coupling agent is Dow Corning 6040;

[0082] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0083] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0084] The thixotropic agent is Wacker H2O.

[0085] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0086] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0087] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0088] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0089] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 35mΩ / □ / mil.

[0090] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 1.8μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0091] Example 3

[0092] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 16.6% solvent, 0.2% coupling agent, 74% silver powder, and 0.25% thixotropic agent.

[0093] The epoxy resin is bisphenol A epoxy resin;

[0094] The curing agent is Asahi Kasei 9322;

[0095] The curing accelerator is CAS: 17501-44-9;

[0096] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0097] The coupling agent is Dow Corning 6040;

[0098] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0099] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0100] The thixotropic agent is Wacker H2O.

[0101] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0102] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0103] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0104] After adding silver powder to the above secondary carrier, the mixture is stirred at 90-1500 rpm on a double planetary mixer. The mixture is then ground by three roller mills, filtered through a 2000-mesh filter press, and the silver paste is then vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0105] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 20mΩ / □ / mil.

[0106] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 0.7μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0107] Comparative Example 1

[0108] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 8% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 11.6% organic solvent, 0.2% coupling agent, 78% spherical silver powder, and 0.25% thixotropic agent.

[0109] The epoxy resin is 50 wt% bisphenol A epoxy resin and 50 wt% bisphenol F epoxy resin;

[0110] The curing agent is Asahi Kasei 9322;

[0111] The curing accelerator is CAS: 17501-44-9;

[0112] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0113] The coupling agent is Dow Corning 6040;

[0114] The organic solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2.

[0115] Spherical silver powder has a D50 of 1-2 μm and a D90 of 3-5 μm.

[0116] The thixotropic agent is Wacker H2O.

[0117] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0118] Epoxy resin and organic solvent are mixed in a glass stirred tank for 15 hours until the resin solution is uniform and fine, without large particles, and serves as a primary carrier. The stirring speed is 350 rpm.

[0119] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0120] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0121] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 43mΩ / □ / mil.

[0122] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 3.5μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0123] Comparative Example 2

[0124] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 15.6% solvent, 0.2% coupling agent, 75% silver powder, and 0.25% thixotropic agent.

[0125] The epoxy resin is 50 wt% bisphenol A epoxy resin and 50 wt% bisphenol F epoxy resin.

[0126] The curing agent is Asahi Kasei K60X;

[0127] The curing accelerator is CAS: 17501-44-9;

[0128] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0129] The coupling agent is Dow Corning 6040;

[0130] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0131] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0132] The thixotropic agent is Wacker H2O.

[0133] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0134] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0135] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0136] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0137] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 65mΩ / □ / mil.

[0138] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 3.5μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0139] Comparative Example 3

[0140] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 8% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 11.6% solvent, 0.2% coupling agent, 78% silver powder, and 0.25% thixotropic agent.

[0141] The epoxy resin is bisphenol A epoxy resin;

[0142] The curing agent is Asahi Kasei 9322;

[0143] The curing accelerator is SA-102;

[0144] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0145] The coupling agent is Dow Corning 6040;

[0146] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0147] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0148] The thixotropic agent is Wacker H2O.

[0149] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0150] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0151] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0152] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0153] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 19.3 mΩ / □ / mil.

[0154] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 2.6μm, and after CP argon ion polishing, the silver paste is layered and there are no pores >3μm.

[0155] Comparative Example 4

[0156] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 8% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 11.6% solvent, 0.2% coupling agent, 78% silver powder, and 0.25% thixotropic agent.

[0157] The epoxy resin is 50 wt% bisphenol A epoxy resin and 50 wt% bisphenol F epoxy resin;

[0158] The curing agent is Asahi Kasei 9322;

[0159] The curing accelerator is SA-102;

[0160] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0161] The coupling agent is Dow Corning 6040;

[0162] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0163] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0164] The thixotropic agent is Wacker H2O.

[0165] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0166] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0167] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0168] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0169] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 43.5 mΩ / □ / mil.

[0170] After three layers of printing, the thickness is 16-20μm and the surface roughness Rz is 3.7μm. After CP argon ion polishing, the silver paste is layered and there are no pores >3μm.

[0171] Comparative Example 5

[0172] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 15.6% solvent, 0.2% coupling agent, 75% silver powder, and 0.25% thixotropic agent.

[0173] The epoxy resin is bisphenol A epoxy resin;

[0174] The curing agent is Asahi Kasei K60X;

[0175] The curing accelerator is SA-102;

[0176] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0177] The coupling agent is Dow Corning 6040;

[0178] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0179] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0180] The thixotropic agent is Wacker H2O.

[0181] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0182] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0183] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0184] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0185] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 36.2 mΩ / □ / mil.

[0186] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 2.2μm, and after CP argon ion polishing, the silver paste is layered and there are no pores >3μm.

[0187] Comparative Example 6

[0188] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 16.6% solvent, 0.2% coupling agent, 74% silver powder, and 0.25% thixotropic agent.

[0189] The epoxy resin is 50 wt% bisphenol A epoxy resin and 50 wt% bisphenol F epoxy resin;

[0190] The curing agent is Asahi Kasei K60X;

[0191] The curing accelerator is SA-102;

[0192] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0193] The coupling agent is Dow Corning 040;

[0194] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0195] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0196] The thixotropic agent is Wacker H2O.

[0197] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0198] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0199] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0200] After adding silver powder to the above secondary carrier, the mixture is stirred at 90 / 1500 rpm on a double planetary mixer. The mixture is then milled in a three-roll mill, filtered through a 2000-mesh filter press, and then the silver paste is vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0201] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 72mΩ / □ / mil.

[0202] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 3.6μm, and after CP argon ion polishing, the silver paste is layered and there are no pores >3μm.

[0203] Comparative Example 7

[0204] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 16.6% solvent, 0.2% coupling agent, 74% silver powder, and 0.25% thixotropic agent.

[0205] The epoxy resin is 50 wt% bisphenol A epoxy resin and 50 wt% bisphenol F epoxy resin;

[0206] The curing agent is Asahi Kasei 9322;

[0207] The curing accelerator is CAS: 17501-44-9;

[0208] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0209] The coupling agent is Dow Corning 6040;

[0210] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0211] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0212] The thixotropic agent is Wacker H2O.

[0213] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0214] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0215] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0216] After adding silver powder to the above secondary carrier, the mixture is stirred at 90-1500 rpm on a double planetary mixer. The mixture is then ground by three roller mills, filtered through a 2000-mesh filter press, and the silver paste is then vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0217] The above conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed that its pencil hardness was ≥3H, adhesion was grade 5B, and sheet resistance was 55mΩ / □ / mil.

[0218] After three layers of printing, the thickness is 16-20μm, the surface roughness Rz is 2.7μm, and after CP argon ion polishing, the silver paste does not separate into layers and there are no pores >3μm.

[0219] Comparative Example 8

[0220] A low-temperature conductive silver paste for an ultrasonic fingerprint module comprises, by weight percentage: 7% epoxy resin, 1.2% curing agent, 0.2% curing accelerator, 0.55% dispersant, 16.6% solvent, 0.2% coupling agent, 74% silver powder, and 0.25% thixotropic agent.

[0221] The epoxy resin is bisphenol A epoxy resin;

[0222] The curing agent is hexafluoroantimonate;

[0223] The curing accelerator is CAS: 17501-44-9;

[0224] The dispersant is a mixture of TDO and oleic acid in a mass ratio of 1.2:1;

[0225] The coupling agent is Dow Corning 6040;

[0226] The solvent is a mixture of DBE and diethyl adipate in a mass ratio of 1:2;

[0227] The silver powder has a D50 of 1-2μm and a D90 of 3-5μm, and is spherical.

[0228] The thixotropic agent is Wacker H2O.

[0229] The preparation method of the low-temperature conductive silver paste for the ultrasonic fingerprint module mentioned above includes the following steps:

[0230] The epoxy resin and solvent were mixed in a glass stirring vessel for 15 hours until the resin solution was uniform and fine, without large particles, and served as a primary carrier. The stirring speed was 350 rpm.

[0231] Add curing agent, curing accelerator, coupling agent, dispersant and thixotropic agent to the obtained primary carrier, mix and then mix at 70 / 1200 rpm on a double planetary mixer; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches below 5 μm, thus obtaining the secondary carrier.

[0232] After adding silver powder to the above secondary carrier, the mixture is stirred at 90-1500 rpm on a double planetary mixer. The mixture is then ground by three roller mills, filtered through a 2000-mesh filter press, and the silver paste is then vacuum dispersed at 500 rpm / 10 min / 2.5 kPa to obtain the desired silver paste.

[0233] The conductive silver paste was screen-printed and dried at 90°C for 60 minutes. Testing showed a pencil hardness ≥4H, adhesion grade 0B, and sheet resistance that could not be measured. Due to insufficient adhesion, it could not be laminated.

[0234] In summary, under the conditions of limiting the solid bisphenol A epoxy resin, the ratio of silver powder with a certain uniform particle size to epoxy resin to be 74:7, and the curing accelerator being zirconium acetylacetonate, the low-temperature conductive silver paste for ultrasonic fingerprint modules prepared has the advantages of curing temperature <90℃, sheet resistance <30mΩ / □ / mil, high density, low surface roughness (Rz <1.5μm), and no delamination or large-sized pores (>3μm) after lamination.

[0235] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A silver paste for an ultrasonic fingerprint module, characterized in that: In terms of weight percentage, the raw materials include: Epoxy resin 2%-15%, curing agent 0.5%-2%, curing accelerator 0.01%-0.5%, dispersant 0.5%-2%, organic solvent 2%-20%, coupling agent 0.1%-0.3%, spherical silver powder 65%-85% and thixotropic agent 0.03%-1.35%; Wherein, the epoxy resin is bisphenol A epoxy resin.

2. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The spherical silver powder is micron-sized silver powder, with a D50 of 1-2 μm and a D100 of 3-5 μm; and / or The mass ratio of the epoxy resin to the spherical silver powder is 7:

74.

3. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The curing accelerator includes a metal salt of acetylacetonate.

4. The silver paste for ultrasonic fingerprint module according to claim 3, characterized in that: The metal salt of acetylacetonate is zirconium acetylacetonate.

5. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The curing agent includes one or more of dicyandiamide, blocked isocyanate or latent imidazole modifier.

6. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The dispersant is one or more of polyether phosphate, oleic acid, TDO or lauryl phosphate.

7. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The organic solvent is one or more of DBE, dimethyl adipate, diethyl adipate, 3-methoxybutyl acetate or propylene glycol methyl ether acetate.

8. The silver paste for ultrasonic fingerprint module according to claim 1, characterized in that: The coupling agent is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a bimetallic coupling agent, a phosphate coupling agent or a borate coupling agent.

9. A method for preparing silver paste for ultrasonic fingerprint module, characterized in that: The following steps are involved: According to the weight percentage of the silver paste raw material according to any one of claims 1 to 8, the epoxy resin and the organic solvent are uniformly mixed to obtain a primary carrier; Adding a curing agent, a curing accelerator, a coupling agent, a dispersant and a thixotropic agent to the primary carrier, stirring once, and then three-roll grinding to obtain a secondary carrier; Spherical silver powder is added to the secondary carrier, stirred twice, ground by three rollers, filtered by a filter press, and then vacuum dispersed to obtain the silver paste.

10. The method for preparing silver paste for ultrasonic fingerprint module according to claim 9, characterized in that: The conditions in the first stirring and the second stirring process are: placing the mixed material in a double planetary mixer and mixing at a speed of 50-100 / 1000-2000rpm; and / or The conditions in the vacuum dispersion process are: dispersion at a speed of 200-1000 rpm for 10-30 minutes under a condition of 1-5 kPa.

Citation Information

Patent Citations

  • Single-component conductive adhesive stored and cured at normal temperature as well as preparation method and application thereof

    CN110964462A

  • Peelable adhesive, and preparation method and application thereof

    CN111635692A

  • Conductive material, ultrasonic fingerprint module and electronic equipment

    CN112016397A

  • Low-temperature conductive silver paste for HJT battery and preparation method of low-temperature conductive silver paste

    CN117410010A

  • Conductive material, ultrasonic fingerprint module, and electronic device

    WO2022021228A1

Cited By

  • Tungsten slurry for ultrasonic fingerprint module and preparation method thereof

    CN121171689A